Assertiveness level of university students - Voltan-Acar, Nilüfer; Aricio?lu, Ahu; Gültekin, Filiz; Gençtanirim, Dilek (My University, 2008)
The aim of this study is to investigate assertiveness of the university students according to their major, kind of ÖSS point, their hometown their mother's-father's attitudes.. The participants of the study were Hacettepe University Foreing Languages School students who attended the summer school in 2006-2007 school year.. Voltan- Acar Assertiveness Scale was administered to determine dependent variable of the study and a questionanaire which was developed by the researhers was utilized to determine the independent variables. SPSS 13 software was used to analyze the data of the study. To compare the dyadic groups t tes•t and to compare the multiple groups one way ANOVA were used. According to the results, the assertiveness levels of the university students significant difference were not found between gender, the OSS points and the place which the students spent most of their lives . There was a significant difference in favor of democratic parental attitude when the assertiveness level of the students were compared. The findings were discussed in the light of the literature.
Üni•versi•te ö?renci•leri•ni•n güvengenli•k düzeyleri•ni•n i•ncelenmesi•
Keywords: Assertivenes; University students; Voltan-acar assertiveness scale